2010
DOI: 10.1111/j.1540-6288.2010.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Gold a Hedge or a Safe Haven? An Analysis of Stocks, Bonds and Gold

Abstract: Is gold a hedge, defined as a security that is uncorrelated with stocks or bonds on average, or is it a safe haven, defined as a security that is uncorrelated with stocks and bonds in a market crash? We study constant and time-varying relations between U.S., U.K. and German stock and bond returns and gold returns to investigate gold as a hedge and a safe haven. We find that gold is a hedge against stocks on average and a safe haven in extreme stock market conditions. A portfolio analysis further shows that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

43
688
2
15

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,746 publications
(748 citation statements)
references
References 18 publications
43
688
2
15
Order By: Relevance
“…Baur and McDermott (2010) investigate the role of gold in the global financial system between the period from 1979 to 2009 and conclude that at times of crisis gold is both a strong safe haven and a hedge for most developed markets, especially the European and the US markets, but not in Japan, Canada, and Australia. In another study, Baur and Lucey (2010) come up with the same results in German, UK and US markets on a data sample ranging from 1995 to 2005. Arouri et al (2012) study gold, silver, palladium and platinum markets and adduce that long memory can explain the conditional volatilities of these commodities far better than structural breaks as the conditional returns and volatilities exhibit a long-range dependence.…”
Section: Literature Reviewmentioning
confidence: 54%
“…Baur and McDermott (2010) investigate the role of gold in the global financial system between the period from 1979 to 2009 and conclude that at times of crisis gold is both a strong safe haven and a hedge for most developed markets, especially the European and the US markets, but not in Japan, Canada, and Australia. In another study, Baur and Lucey (2010) come up with the same results in German, UK and US markets on a data sample ranging from 1995 to 2005. Arouri et al (2012) study gold, silver, palladium and platinum markets and adduce that long memory can explain the conditional volatilities of these commodities far better than structural breaks as the conditional returns and volatilities exhibit a long-range dependence.…”
Section: Literature Reviewmentioning
confidence: 54%
“…Baur and Lucey (2010) were the first to formulate empirically testable definitions for a hedge and a safe haven with regard to financial assets such as stocks. Following their definitions, a hedge (safe haven) is an asset that is uncorrelated (negatively correlated) with another asset or portfolio on average (only in times of market stress or turmoil) (Beckmann et al 2015) and reported that gold was a safe haven for stocks in the US, the UK and Germany.…”
Section: Related Literaturementioning
confidence: 99%
“…The empirical analysis by Baur and Lucey (2010), shows that gold is a safe haven for stocks in U.S., U.K., and Germany as earlier studies shows, but not a safe haven to bonds. After they done a subsample analysis into bull and bear market regime, the interesting finding was that gold is not a safe haven for stocks at all times, but only after extreme negative stock market shocks, by finding gold estimates highly significant in bear market in all three markets analyzed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent study by Baur and Lucey (2010) tested whether gold is safe haven asset, not hedge or diversifier asset. According to authors, they are not aware of any study actually testing whether gold is a safe haven asset.…”
Section: Literature Reviewmentioning
confidence: 99%